When is the Time of Revolution? Critical Reflections on Political Insurgency. (September 2017) - Olson, Kevin
Abstract: We tend to imagine revolution as a vivid tableau of uprisings and armed conflicts. Much less notice is taken of the complex layers of meaning that shape our understanding of these events: why some are seen as just expressions of a popular will, while others are condemned as wild disruptions of political order. A critical understanding of politics must grapple with these subtle, often unnoticed normative issues. This essay tries to understand some of the processes that create political normativity, investigating the way revolutionary movements use time to endow themselves with normative value. I sketch a genealogy of revolution across three centuries, noting changes in its meaning, observing the rise of discourse as an important mode of revolutionary activity, and tracing a shifting mosaic of temporalities that are politicized in important ways. Time is instrumentalized to justify political insurgency in this history. Time, in short, becomes a tool of revolution.